Transformation and sustainability in agriculture Connecting practice with social theory - Vellema, Sietze; SpringerLink (Online service) (Wageningen : Wageningen Academic Publishers : Imprint: Wageningen Academic Publishers, 2011)
Public pressure and societal changes induce interventions and policies, which aim to transform agriculture and food provision. This book shows that for upscaling novel practices and organizational models it is important to include meso-level regime aspects in analysis and practice. The argument presented is that our understanding of the human and social dimensions of transformation processes can be enriched by anchoring practice and policy in social theory. A focus on transitions offers a clear view on the direction and velocity of change. This publication aims to complement this by highlighting theoretical insights in the social or institutional mechanisms enabling or hindering change. Essays on a selection of theorists, varying from idealist or materialist accounts, to actor or system approaches, examine what the presented explanatory framework on social change offers in terms of guidance for intervention and action. The value of these theoretical insights is further explored in a selection of case studies in agriculture and food: rural reconstruction in horticulture and livestock, seed supply systems, and pest control. Each case study systematically applies six theoretical frameworks with the purpose of investigating what novel insights arise from looking at the change process from a particular perspective. Through this exercise the often implicit assumptions of hands-on change processes surface. This book is of interest to practitioners engaged in changing current practices in agriculture and food provision, policy makers interested in grasping why transitions are challenging, applied researchers who like to move beyond individual case studies and social and natural scientists involved in integrative studies of complex change processes.
Acknowledgements -- 1. Transformation and sustainability in agriculture: connecting practice with social theory; S. Vellema -- 2. New institutional economics: Douglass North and Masahiko Aoki; G. Meijerink -- 3. Social systems and social engineering: Niklas Luhmann; K. van Assche et al -- 4. The role of social networks: Mark Granovetter; M. Reinders -- 5. Doubt management as a tool for change: Karl E. Weick; T. Selnes, C. Termeer -- 6. Power and discipline in transitions: Michel Foucault; M. Duineveld, G. Dix -- 7. Materiality, nature and technology in agriculture: Ted Benton; S. Vellema -- 8. Sustainable greenhouse horticulture and energy provision: two regional transition processes compared; J. Buurma, M. Ruijs -- 9. The reconstruction of livestock farming in the Netherlands; C. de Lauwere, S. Vellema -- 10. Seed provision in developing economies: converting business models; R.C. Wiersinga et al -- 11. Changing the crop protection or pesticide use regime in the Netherlands: an analysis of public debate; J. Buurma -- Contributors.
Keywords: Life sciences; Life Sciences; Life Sciences, general